Fatores psicossociais e a percepção familiar sobre a saúde dental de crianças pré-escolares - Rigo, Danielle Cristina Alves (2020)
Introduction: Maternal perception of children's dental health has been investigated, however, knowledge about children in pre-school age is still scarce and the influence of maternal psychosocial factors is not known. Objective: To analyze the maternal perception about the dental health of his/her child at preschool age and associated factors. Methodology: Cross- sectional study. The sample consisted of 146 mother-child dyads from 4 to 6 years old, attending dental clinics of two specialization courses in Pediatric Dentistry in Goiânia, Goiás, in 2018 and 2019. Data collection instruments were an structured interview form and a questionnaire with dental and psychosocial scales for mothers, as well as a form to register data from the children's clinical records. Maternal perception about the child's dental health was the outcome variable, categorized as positive (very good and good) and negative (neither good nor bad, bad and very bad). The independent variables were related to mothers (sociodemographic, oral health-related and psychosocial) and children (sociodemographic and oral health-related). Data analysis consisted of descriptive statistics, bivariate tests and Poisson Regression. Results: Most mothers had a negative perception of their child's dental health (54.8%). In the bivariate analysis, the perception was associated with the child's caries experience (ceo-d index) and the report of dental pain at some time in life (p <0.05). In the non-adjusted regression these variables were included as well as the other independent variables associated to the outcome with p values <0,25. In the adjusted regression model, Organizational Religiosity (RO) and the child's caries experience were associated with the outcome, regardless of the other variables (p <0.05). The proportion of mothers with negative perception of their children's dental health was 1.45 higher in the group with low OR (PR = 1.45; 95% CI 1.10-1.91) and 2.31 higher in the group of children with high caries experience (PR = 2.31; 95% CI 1.50-3.54). The other variables were not associated with the outcome. Conclusions: The maternal perception about the dental health of the preschool child was predominantly negative and associated with the mother's religiosity and the child's caries experience.